2020
DOI: 10.1371/journal.pone.0240152
|View full text |Cite|
|
Sign up to set email alerts
|

Stigma in coronavirus disease-19 survivors in Kashmir, India: A cross-sectional exploratory study

Abstract: Background Coronavirus disease-19 (COVID-19) has not only spawned a lot of stigma and discrimination towards its survivors but also to their corpses. We aimed to assess the magnitude and correlates of stigma in these survivors, on return to their communities. Methods This was a cross-sectional, hospital-based, exploratory study conducted by the postgraduate department of psychiatry, in collaboration with the postgraduate department of chest medicine, Govt. medical college, Srinagar. The study was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 40 publications
6
101
2
Order By: Relevance
“…SARS and MERS survivors suffered not only from physical ramifications (reduced exercise capacity and lung function) but also from mental health impairment (anxiety and depression) [9]. Similarly, owing to the stigma associated with COVID-19, the survivors face constant shaming and discrimination, adding a psychological component to their physical suffering [10]. However, with most current literature focused on the acute management of COVID-19, data regarding post-COVID-19 manifestations are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…SARS and MERS survivors suffered not only from physical ramifications (reduced exercise capacity and lung function) but also from mental health impairment (anxiety and depression) [9]. Similarly, owing to the stigma associated with COVID-19, the survivors face constant shaming and discrimination, adding a psychological component to their physical suffering [10]. However, with most current literature focused on the acute management of COVID-19, data regarding post-COVID-19 manifestations are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Nepal revealed stigmatisation of frontline health workers (19). A quantitative survey of 91 people who had survived Covid-19 infection in Kashmir, India, showed a high level of enacted and externalised stigma ie stigma which is a consequence of social interactions of the infected persons (20). However, there are not many qualitative interview-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…Dar SA, Khurshid SQ, Wani ZA, Khanam A, Haq I, Shah NN, et al (2020) Correction: Stigma in coronavirus disease-19 survivors in Kashmir, India: A cross-sectional exploratory study. PLoS ONE 15(12): e0244715.…”
mentioning
confidence: 99%